Do Mergers Result in Collusion? - Mattias Ganslandt; Pehr-Johan Norbäck (The Research Institute of Industrial Economics (IUI), 2004)
We examine coordinated effects of mergers in the Swedish retail market for gasoline during the period 1986-2002. Despite significant changes in market concentration and many factors conductive to coordination, the empirical analysis shows that the level of coordination is low. In addition, statistical tests reject the hypothesis that mergers and acquisitions result in coordinated effects. In particular, higher market concentration does not result in more collusive behavior and, consequently, the relevance of simple checklists in merger control can be questioned.
Keywords: D43; L13; L41; 330; Merger Control; Collusion; Coordinated Effects; Oligopolistic Dominance; Competition Policy; Fusion; Kartell; Fusionskontrolle; Benzin; Preis; Schweden